Abnormally increased carotid intima media-thickness and elasticity in patients with Morquio A disease - Wang, Raymond Y. (Orphanet J Rare Dis, 2020)
BACKGROUND: Cardiovascular disease frequently causes morbidity and mortality in mucopolysaccharidoses (MPS); however, cardiovascular anatomy and dysfunction in MPS IVA (Morquio A disease) is not well described. Consequently, the study aimed to compare carotid artery structure and elasticity of MPS IVA patients with other MPS patients and healthy control subjects, and quantitate frequency of MPS IVA cardiac structural and functional abnormalities. METHODS: Prospective, multi-center echocardiogram and carotid ultrasound evaluations of 12 Morquio A patients were compared with other MPS and healthy control subjects. Average differences between groups were adjusted for age, sex, and height with robust variance estimation for confidence intervals and P-values. RESULTS: Morquio A patients demonstrated significantly higher (P < 0.001) adjusted carotid intima-media thickness (cIMT), mean (SD) of 0.56 mm (0.03) compared to control subjects, 0.44 mm (0.04). The Morquio A cohort had significantly greater adjusted carotid elasticity (carotid cross-sectional compliance + 43%, P < 0.001; carotid incremental elastic modulus − 33%, P = 0.003) than control subjects and other MPS patients. Aortic root dilatation was noted in 56% of the Morquio A cohort, which also had highly prevalent mitral (73%) and aortic (82%) valve thickening, though hemodynamically significant valve dysfunction was less frequent (9%). CONCLUSIONS: Increased carotid elasticity in Morquio A patients is an unexpected contrast to the reduced elasticity observed in other MPS. These Morquio A cIMT findings corroborate MPS IVA arterial post-mortem reports and are consistent with cIMT of other MPS. Aortic root dilatation in Morquio A indicates arterial elastin dysfunction, but their carotid hyperelasticity indicates other vascular intima/media components, such as proteoglycans, may also influence artery function. Studying MPS I and IVA model systems may uniquely illuminate the function of glycosaminoglycan-bearing proteoglycans in arterial health.